Identification of ACTA2 as a Key Contributor to Venous Malformation - Wang, Song; Zhou, Zifu; Li, Jing; Wang, Yu; Li, Hongwen; Lv, Renrong; Xu, Guangqi; Zhang, Jian; Bi, Jianhai; Huo, Ran (Frontiers in Cell and Developmental Biology, 2021)
Objectives: Proteomics and high connotation functional gene screening (HCS) were used to screen key functional genes that play important roles in the pathogenesis of venous malformation, analyze and explore their possible functions, establish a gene mutation zebrafish model, and perform a preliminary study to explore their possible pathogenic mechanisms in venous malformation. Methods: Pathological and normal tissues from patients with disseminated venous malformation were selected for Tandem Mass Tag (TMT) proteomics analysis to identify proteins that were differentially expressed. 20 proteins with significant differential expression were selected for HCS to find key driver genes. In vitro cellular functional assays were then performed using human microvascular endothelial cell (HMEC) models. A gene mutant zebrafish model was also constructed for in vivo experiments to explore gene functions and pathogenic mechanisms. Results: The TMT results showed a total of 71 proteins that were differentially expressed as required, with five of them upregulated and 66 downregulated. HCS screening identified ACTA2 as the driver gene. qPCR and western blot were used to detect the expression of ACTA2 in the pathological tissues of patients with venous malformations and in control tissues, and the experimental results showed a significantly lower expression of ACTA2 in venous malformation tissues (P<0.05). Cell assays on the HMEC model showed that cell proliferation, migration, invasion, and angiogenic ability were all slightly but not significantly increased in the ACTA2 overexpression group, and that overexpression of ACTA2 could improve the inhibitory effect on vascular endothelial cell proliferation. We constructed an ACTA2-knockdown zebrafish model and found that the knockdown of ACTA2 resulted in defective vascular development, disruption of vascular integrity, and malformation of microvein development in zebrafish. Further qPCR assays revealed that the knockdown of ACTA2 inhibited the Dll4/notch1 signaling pathway, Ephrin-B2 signaling pathway, and vascular integrity-related molecules and activated the Hedgehog signaling pathway. Conclusions: This study revealed that ACTA2 deficiency is an important factor in the pathogenesis of venous malformation, resulting in the disruption of vascular integrity and malformed vascular development. ACTA2 can be used as a potential biomarker for the treatment and prognosis of venous malformations.